Modified nusinersen intrathecal injection method: inclusion of a septal needle-free closed infusion connector - Zhang, Yani; Zheng, Kelu; Liang, Cuili; Zheng, Ruidan; Chen, Jinghui; Jiang, Minyan; Zhou, Zhizi; Zhao, Yuan; Rao, Min; Yang, Sida; Chen, Wenxiong; Liu, Li (Frontiers in Neurology, 2023)
Objective: Nusinersen, an extremely expensive biologic drug (around 10,0000 US per dose) that needs to be administered intrathecally, is approved for the treatment of 5q-spinal muscular atrophy (SMA). Because of low muscle tone of back muscles of pediatric SMA patients, especially type 1 SMA patients, the safe, effective, and fast execution of sheath injection is needed. Therefore, a modified intrathecal injection method was developed accordingly. This paper aimed to describe the applicability and safety of this modified method. Methods: The modified intrathecal injection method mainly includes a septal needle-free closed infusion connector between the lumbar puncture needle and syringe, with the exception of the procedures of routine lumbar puncture. Its applicability and safety were evaluated through clinical observation. Results: A total of 92 children with SMA have successfully received nusinersen treatment at our hospital using the modified method since 2019, without obvious adverse events related to the modified injection method. The advantages of the modified method included successfully injecting total dose of nusinersen with constant injection rate and more stable fixation of puncture needle as well as making the operator more relaxed, based on the clinical feedback of operators. However, compared with the routine method, the procedure of the modified method has additional steps. Conclusion: The modified intrathecal injection method is an effective and safe method to inject nusinersen when weighting the pros and cons, and it may also be used for administering intrathecal injections of other expensive medicines, or for patients with other strict requirements for intrathecal injection.